Digital libraries and information services - Bajpai, R. P. (Shree, 2004)
Contents of material: 1/ Digital libraries and information services. 2/ Digital libraries and World Wide Web. 3/ Net-oriented information. 4/ Modern library classifications. 5/ Online library management. 6/ Linking online resources.